Risk management, corporate governance, and business continuity of pharmacies in D.I.Yogyakarta and Sleman Regency - Henrika, Margareth; Yudianti, Francisca Ninik; Anggraini, Reni Retno (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2025)
This research investigates the influence of risk management and corporate governance on the business continuity of pharmacies in Yogyakarta City and Sleman Regency. The objective is to assess the impact of these factors on the long-term sustainability of pharmacies, with a focus on how risk management moderates the effect of corporate governance. A quantitative approach using descriptive methods was employed, with data collected via a simple random sampling technique and analyzed using SPSS version 24. The study utilized both simple linear regression and Moderated Regression Analysis (MRA). Results revealed that risk management significantly impacts the continuity of pharmacy businesses, while corporate governance alone does not have a direct effect. Furthermore, risk management was found to effectively moderate the influence of corporate governance on business sustainability. The findings emphasize that effective risk management practices strengthen the role of corporate governance in ensuring the continued success of pharmacies. These insights provide valuable guidance for pharmacy managers seeking to improve their operational resilience and competitiveness in a challenging market environment.